Enhancing English skills of Islamic communication and broadcasting students with public speaking: opportunities and challenges - Suciati; Ihya Nur Syamsiani (Erudita: Journal of English Language Teaching, 2025)
This study aims to explore the opportunities and challenges faced by students in the Islamic Communication and Broadcasting (ICB) Study Program as they strive to improve their English public speaking skills and to explain the strategies employed by both students and lecturers in overcoming these challenges. This study was motivated by the gap between English language learning, which previously focused on grammar and reading, and the real needs of ICB students in public speaking in the context of Islam and media. This study used a qualitative approach with a classroom-based research design involving 31 students in the study program. Data were collected through observation, interviews, and document analysis and analyzed thematically. The study findings demonstrate three main findings: (1) learning public speaking based on professional contexts opens up great opportunities to increase student participation, self-confidence, and communicative abilities, (2) main challenges include speaking anxiety, limited vocabulary, and lack of authentic exposure, and (3) effective strategies include a task-based approach, the use of digital technology, and active collaboration between lecturers and students. This finding confirms the need to develop a contextual and integrative English for specific purposes (ESP) curriculum for ICB students.